Workers and Dissent in the Redwood Empire - Cornford, Daniel A. (Temple University Press, 1987)
In the history business, calling a work a classic can be a double-edged sword. Daniel Cornford's book is a classic in the best way. His analysis of California's redwood forests and those who turned them into lumber is a finely wrought piece of historical scholarship. Workers and Dissent in the Redwood Empire focuses attention on a place that needed more study, the redwood forest belt of far northern California. It excavates a period either hidden or removed from view, the second half of the nineteenth century and the first few decades of the twentieth. Cornford connects California's story of "gold and mineral" to "red and wood," mxing high drama amidst those impossibly tall trees: trouble in the guise of Labor versus Capital tensions; tugs of war over power, pay, and work conditions; and no small amount of violence. It is all done in the form of a careful, scholarly reckoning, with many chapters and many footnotes, all tightly wound around a scholarly narrative that explains place and nature, labor and capital, in ways that bring our understanding of Gilded Age troubles into a dark forest where very few of us would think to look.